Effects of Preoperative Mean Platelet Volume on Early Outcomes of Patients After Conventional Coronary Artery Bypass Graft Surgery - Hasan, Md Amirul; Milon, Md Kamrul Hasan; Kashem, Md Abul; Karim, Md Rezaul (University Heart Journal, 2018)
An elevated mean platelet volume is associated with increased platelet activation and thus may predict thrombotic events including major cardiac adverse events after CABG surgery. The association of mean platelet volume with in-hospital outcome of patients after coronary artery bypasses grafting surgery was investigated in this study. Preoperative mean platelet volume was obtained prospectively in 8^ consecutive patients undergoing conventional coronary artery bypass surgery. Postoperative mortality and major adverse events were recorded in the early postoperative Period. Combined adverse events including post operative Myocardial Infarction (Ml), arrhythmia, bleeding and death occurred in 27 patients (33.3%) during the early follow-up. The preoperative mean platelet volume levels were found to be associated with postoperative adverse events (p<0.05). In multivariate logistic regression models, the preoperative mean platelet voluue levels was found strong independent predictor of combined adverse events after surgery (OR 1.968, p=0.008). University Heart Journal Vol. 14, No. 1, Jan 2018; 24-27